Use of hydraulic modeling to evaluate hose systems - Ścieranka, Grzegorz (Instal, 2022)
The paper presents hydraulic calculations results of an exemplary hose systems with the use of hydraulic modeling in EPANET software. The relationship between the K coefficient of hydrants and the C emitter coefficient used to simulate leak flow in EPANET was determined. It has been shown that the calculation method has an impact on the hydraulic parameters of the water source.